Managing the Internet of Things : architectures, theories and applications - Huang, Jun; Hua, Kun (IET telecommunications series ;, 2016)
The implementation and deployment of the Internet of Things (IoT) brings with it management challenges around seamless integration, heterogeneity, scalability, mobility, security, and many other issues. This comprehensive book explores these challenges and looks at possible solutions.